PERAN EFIKASI DIRI DAN SCHOOL BELONGINGNESS TERHADAP PERMASALAHAN EMOSI DAN PERILAKU REMAJA - Ridho Salsabiela, Nur Amanah; Saptandari, Edilburga Wulan (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
This decade, Emotional Behavior Problems (EBP) among teenagers shows a prevalence rate that tends to be high both globally and nationally. Self-efficacy and school ownership are assessed as predictors of EBP, so this research aims to determine the negative role of self-efficacy and school ownership on Emotional Behavioral Problems (EBP) of adolescents who are junior high school (SMP) students. A total of 169 students of SMPN X and SMPN Y in Yogyakarta City were participants in this research. Participants were taken using purposive sampling technique. The instruments used in this research are three scales which include the Strengths and Difficulties Questionnaire (SDQ), General Self-Efficacy (GSE), Psychological Sense of School Membership (PSSM). Multiple linear regression analysis showed that self-efficacy and sense of school belonging simultaneously could not predict EBP. Meanwhile, separate predictor analysis was able to predict EBP. Additional analyzes showed no significant differences in EBP by gender, grade level, or family condition Dekade ini, Emotional Behavioral Problem (EBP) di kalangan remaja menunjukkan angka prevalensi yang cenderung tinggi baik dalam lingkup global maupun nasional. Efikasi diri dan school belongingness dinilai dapat menjadi prediktor EBP sehingga penelitian ini bertujuan untuk mengetahui peran negatif efikasi diri dan school belongingness terhadap Emotional Behavioral Problem (EBP) remaja yang merupakan siswa Sekolah Menengah Pertama (SMP). Sebanyak 169 siswa SMPN X dan SMPN Y di Kota Yogyakarta menjadi partisipan dalam dalam penelitian ini. Partisipan diambil menggunakan teknik purposive sampling. Instrumen yang digunakan dalam penelitian ini adalah tiga skala yang meliputi The Strengths and Difficulties Questionnaire (SDQ), General Self-Efficacy (GSE) Psychological Sense of School Membership (PSSM) Analisis regresi linier berganda menunjukkan bahwa efikasi diri dan school belongingness secara simultan tidak dapat memprediksi EBP. Sementara itu, analisis prediktor secara terpisah mampu memprediksi EBP. Analisis tambahan menunjukkan tidak ada perbedaan EBP yang signifikan berdasarkan jenis kelamin, tingkatan kelas, atau kondisi keluarga